Parental tobacco consumption and child development - Nadine F. Santos; Raquel A. Costa (Brazilian Society of Pediatrics, 2015)
Objective: To analyze the association between parental tobacco consumption and the prevalence of psychomotor development disorders in children between 6 and 22 months of age. Method: One hundred and nine mothers, fathers, and their babies participated in the study. The sociodemographic and clinical conditions were assessed using questionnaires. Tobacco consumption was assessed using the Fagerström Test for Nicotine Dependence (FTND). Child development was evaluated using the Scale of Psychomotor Development in Early Childhood. Results: There was a significant negative correlation between the father's morning smoking (FTND) and the child's language development quotient; r = −0.41, p = 0.005, r2 = 0.15. The children of mothers without nicotine dependence had a higher mean language development quotient than children of mothers with nicotine dependence; F(1, 107) = 5.51, p = 0.021, ηp2 = 0.05. Conclusion: Parental smoking appears to have a detrimental effect on child development.